A new shift mechanism for micro-explosion of water-diesel emulsion droplets at different ambient temperatures. (1st October 2022) - Wang, Zhaowen; Yuan, Bo; Cao, Junhui; Huang, Yuhan; Cheng, Xiaobei; Wang, Yuzhou; Zhang, Xinhua; Liu, Hao
Graphical abstract: Highlights: Bubble formation and micro-explosion modes of water emulsified diesel droplets were studied. Bubble nucleation changed from single site to multiple sites as ambient temperature increased. Bubble nucleation sites shifted from droplet center to surface as ambient temperature increased. Expansion intensity of droplet volume could describe the bubble formation process. Bubble formation and micro-explosion determined the evaporation behavior of fuel droplets. Abstract: Water emulsified diesel is an ideal new alternative fuel for diesel engines, which has great potentials in reducing NOx and PM emissions simultaneously. A thorough understanding of its evaporation process is critical for achieving the emission reduction potentials. Therefore, this study investigated the evaporation characteristics of emulsion droplets with 65% diesel, 30% water and 5% surfactant by mass using the droplet suspension technology at ambient temperature 573–873 K. The normalized squared diameter, micro-explosion frequency, micro-explosion intensity and expansion intensity were used to quantify the effect of ambient temperature on the evaporation characteristics. The results showed that the evaporation process of water emulsified diesel droplets mainly included three stages, namely transient heating, fluctuation evaporation, and equilibrium evaporation. The maximum normalized squared diameter first increased with ambient temperature and then decreased, leading to a maximum of 2.91 at 773 K. The micro-explosion frequency first decreased and then increased, which was consistent with that of micro-explosion intensity. In addition, this study innovatively correlated the internal relationship between bubble formation and micro-explosion. Based on this, a new micro-explosion shift mechanism of water emulsified diesel droplets was proposed. As the ambient temperature increased, bubble nucleation in the droplet gradually changed from single site to multiple sites, and the nucleation sites shifted from the droplet center to surface.